Kreativitas Dalam Penyampaian Katekese Digital Untuk Membangun Pengalaman Berarti - Floriana Doa; Emmeria Tarihoran (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Creativity in delivering digital catechesis plays an important role in building meaningful experiences for people in the modern era. This research uses a qualitative approach with in-depth interviews and participant observation. In this article, we discuss how creativity can enrich the religious experience of individuals, especially the younger generation who are accustomed to technology. The use of digital media allows catechesis to be more interesting and easy to remember. In addition, this article highlights the importance of compiling catechetical materials that are relevant, touching, and inspiring. By utilizing technology well and wisely, churches and catechetical teachers can create space for reflection, dialogue, and deeper spiritual growth. Creativity in digital catechesis is not only about introducing religious values in a modern way, but also building a strong connection between individuals and their spiritual beliefs. Thus, creativity in delivering digital catechesis allows people to experience a deeper, more meaningful and relevant religious experience in the ever-changing digital era.